Komunikasi Singkat: Analisis kualitas minyak atsiri daun Melaleuca trichostachya Lindl. dan daya hambatnya terhadap jamur Candida albicans - Mirayanti, Komang Ayu; Arpiwi, Ni Luh; Wibawa, I Putu Agus Hendra (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2022.v26.i02.p13, 2022)
Melaleuca trichostachya Lindl. is a plant belongs to the family Myrtaceae which originates from of Australia. The leaf of this plant contains sessential oils. One of the biological activities of essential oils is as an antifungal. The aims of the study were to determine the yield of essential oils of M. trichostachya leaf, to analyze oil quality, chemical compounds, and the inhibition of essential oils on the fungi’s of Candida albicans . Fresh and dried M. trichostachya leaf as much as 200 g were extracted by steam distillation method with 3 replications. The essential oil content was calculated, the quality was tested, the chemical compounds were analyzed by Gas Chromatography Mass Spectrometry (GC-MS). The inhibition of essential oil against C. albicans was tested with paper discs on PDA media with a concentration of 25% w/w.  The results showed that the yield of essential oil of M. trichostachya fresh leaf was 1.00±0,058% while the yield of dried leaf was lower, which was 0.77±0,038%. The quality of essential oils was good in terms of organoleptic, purity, and acid numbers. The main compound consists of eucalyptol and alpha terpinolene and has inhibitory power against the fungus C. albicans .